Advancing geotechnical engineering via sustainable biomass-based soil stabilization - Ng, Jun Shen; Muzamir, Hasan; Yap, Wan Er; Hoque, Md. Ikramul (Peter the Great St. Petersburg Polytechnic University, 2025)
This research investigates the potential influence of mixing biomass resources, cow bone ash, in various percentages into the untreated kaolinitic soil in altering the geotechnical parameters. The nature of clayey soil frequently triggers the prevailing issues, such as uneven settlement, insufficient soil-bearing capacity, and abnormal compressibility coefficient. Several fundamental laboratory approaches were deployed to obtain information on grain size distribution, consistency limits, proctor behaviors, and specific gravity. The optimum moisture content of kaolin stabilized with cow bone ash was discovered at 6%, and this value was utilized for the assessment of unconfined compression data. The examination of shear strength parameters was implemented via the fabrication of a cylindrical sample, dimensioned at 38 mm in diameter and 76 mm in height. The kaolin samples were altered using 3%, 6%, 9%, and 12% of cow bone ash content, and cured for periods of 7 and 14 days, respectively. The discoveries revealed that associating all portions of cow bone ash enhanced the kaolin shear strength significantly, ranging from 81.15% to 578.10%. The accuracy was verified by the utilization of the correlation technique, where all the curing periods of the samples possess a coefficient of determination greater than 0.9. Furthermore, the establishment of cost-analysis calculation generates a thorough framework for optimizing the total cost of stabilization, with the efficiency reaching 49.56%. In short, using cow bone ash in soil stabilization resulted in positive implications that advance the technology of the geotechnical industry, proposing a promising development practice via the application of sustainable material.